Prevention of cisplatin‐induced hearing loss in children: Informing the design of future clinical trials. (30th May 2018) - Minasian, Lori M.; Frazier, A. Lindsay; Sung, Lillian; O'Mara, Ann; Kelaghan, Joseph; Chang, Kay W.; Krailo, Mark; Pollock, Brad H.; Reaman, Gregory; Freyer, David R.
Abstract: Cisplatin is an essential chemotherapeutic agent in the treatment of many pediatric cancers. Unfortunately, cisplatin‐induced hearing loss (CIHL) is a common, clinically significant side effect with life‐long ramifications, particularly for young children. ACCL05C1 and ACCL0431 are two recently completed Children's Oncology Group studies focused on the measurement and prevention of CIHL. The purpose of this paper was to gain insights from ACCL05C1 and ACCL0431, the first published cooperative group studies dedicated solely to CIHL, to inform the design of future pediatric otoprotection trials. Use of otoprotective agents is an attractive strategy for preventing CIHL, but their successful development must overcome a unique constellation of methodological challenges related to translating preclinical research into clinical trials that are feasible, evaluate practical interventions, and limit risk. Issues particularly important for children include use of appropriate methods for hearing assessment and CIHL severity grading, and use of trial designs that are well‐informed by preclinical models and suitable for relatively small sample sizes. Increasing interest has made available new funding opportunities for expanding this urgently needed research. Abstract : Cisplatin, an essential chemotherapeutic agent in the treatment of many pediatric cancers, frequently causes hearing loss. Cisplatin‐induced hearing loss can result in long‐term disability. This paper describes issues in the design of otoprotection clinical trials in children.